MINERALOGICAL CHARACTERIZATION OF SOILS REPRESENTING THE CLAY PLAIN OF SUDAN - P.K, Deng; P.W, Marchelo-d’, Ragga (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
Soil profiles were dug in the clay plains of Sudan and six profiles were selected in a transect from East ofRahad River, across Gezira, and west of the White Nile. The objectives of this study were to investigatethe clay mineralogical characteristics of these soils, mineralogical forms and soil samples according togenetic horizons. Twenty four soil samples and four genetic horizons were selected from the six soilprofiles; and were selected for identification of clay mineralogy by X-ray diffraction technique (clayfraction method). The analysis of clay minerals was performed in two steps; the first step was theseparation of less than 2µ clay size fraction and the second step was the X-ray technique itself. Results onmineralogical investigations for the primary clay revealed high content of quartz, and muscovite whichwere also observed in the clay fraction of the soils. Proportions of smectite, kaolinite with relativelyhigher values of smectite especially in the sub-soils were recorded, Illite and chlorite was lower. Part ofthe White Nile and the remaining soils have been derived from the Ethiopian plateau which is dominatedby basic and ultra basic rocks; these rocks are dominant in smectite clays. Quartz, Muscovite and Illite arethe main primary minerals in the studied soils with minor amounts of Zeolite, Pyroxene and Calciteminerals. The clay minerals showed Smectite, Kaolinite, Illite and Chlorite in variable amounts. From theabove results, we can conclude that the identified clay minerals in the studied soils are detrital andoriginated from the Ethiopian Plateau and later on have mixed with limestone material duringtransportation